Pengaruh Intellectual Capital, Zakat Performance Ratio, dan Non-Performing Financing terhadap Kinerja Keuangan Bank Umum Syariah di Indonesia dengan Good Corporate Governance sebagai Variabel Moderasi - Fatmasari, Fatmasari; Hermawan, Sigit; Maryanti, Eny; Biduri, Sarwenda (Journal of Culture Accounting and Auditing, 2026)
This study aims to examine the effect of Intellectual Capital, Zakat Performance Ratio, and Non-Performing Financing on financial performance, with Good Corporate Governance as a moderating variable in Islamic Commercial Banks. This study used secondary data from the financial statements of Islamic Commercial Banks registered with the Financial Services Authority (OJK) during 2019–2024. The sample consisted of 50 observations selected using purposive sampling. Data were analyzed using SPSS 26. The results show that Intellectual Capital and Non-Performing Financing have a negative and significant effect on financial performance, while Zakat Performance Ratio has a positive and significant effect. Good Corporate Governance weakens the effect of Intellectual Capital and Non-Performing Financing but strengthens the effect of Zakat Performance Ratio on financial performance. These findings indicate that resource management, social responsibility, financing quality, and governance influence the financial performance of Islamic Commercial Banks.